Exercise-induced vasculitis and amlodipine - Lachapelle, J.; Ramelet, Anne-Sylvie (2014)
Exercise-Induced vasculitis is an often-unrecognized or misdiagnosed clinical entily, despite its frequency and clear-cut symptoms. This condition is characterized by pruritic and discretely painful erythematous and purpuric lesions, which are more or less sharply demarcated, on the medial and posterior aspects of the legs, (I.e. sparing the upper-third of the legs and the malleolar areas). These lesions manifest themselves after a sustained walk. Their key histopa-thological features often resemble those of leucocytoclastic vasculitis. The lesions disappear spontaneously after approximately 10 days. In the present case, prior treatment by amlodipine resulted in marked edema of the ankles, along with features of vasculitis, occurring after a very short walk, which is rather uncommon.